The usefulness of walnut shells as waste biomass fuels in direct carbon solid oxide fuel cells. (December 2018) - Dudek, Magdalena; Adamczyk, Bartosz; Sitarz, Maciej; Śliwa, Michał; Lach, Radosław; Skrzypkiewicz, Marek; Raźniak, Andrzej; Ziąbka, Magdalena; Zuwała, Jarosław; Grzywacz, Przemysław
Abstract: Raw and charred walnut shells were investigated as solid fuels in direct carbon solid fuel cells operating within the temperature range 600–850 °C. Char was prepared by means of thermal processing of pulverised shells in a quartz reactor within a temperature range of 400–850 °C. Elemental analysis identified high carbon and marginally low sulphur contents in char obtained from biomass-derived solid waste. With increased temperatures, a greater degree of carbonisation of raw material was observed in the char, along with reduced sulphur and hydrogen contents. XRD and Raman spectroscopy investigations showed that the char samples were characterised by a disordered carbon structure. The particles were characterised by the presence of smaller isometric particles as well as a porous structure. Thermogravimetric analysis performed in a pure CO2 gas atmosphere within a temperature range of 25–850 °C demonstrated a substantial loss of mass due to CO production via the Boudouard reaction. Tests showed that DC-SOFCs supplied by char obtained from walnut shells were characterised by stable operation with reasonably satisfactory levels of current and power density. A significant improvement was noted in the performance of a DC-SOFC supplied by all forms of char when CO2, as opposed to N2, was used as the shielding gas in the anode chamber. Highlights: Electricity can be generated from fuel cells supplied by walnut shells. The lower temperature of chars was obtained, the better power output of DC-SOFC was recorded. The oxidation of carbon in the DC-SOFC analysed according to the "shuttle mechanism". The cathodes also improved the performance of the DC-SOFC.